(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2025)
This study provides a comprehensive bibliometric analysis of research on the alignment of organizational values, person–organization fit, work engagement, and subjective wellbeing. Utilizing the Web of Science core collection, we examined 152 relevant publications to understand the intellectual structure, evolution, and emerging trends in this interdisciplinary field. The analysis highlights the significant contributions from diverse disciplines, including psychology and business economics, and identifies key research clusters and influential authors. Our findings reveal that alignment of organizational values and person–organization fit are crucial for enhancing employee engagement, satisfaction, and overall well-being, which in turn improve organizational performance. The study also underscores the importance of fostering strong organizational cultures to support employee health and productivity. Furthermore, the research identifies gaps in the current literature, particularly in the underrepresentation of Asian contexts, and suggests the need for future studies to incorporate quantitative methodologies and explore multidisciplinary approaches. This analysis serves as a valuable resource for academics and professionals seeking to advance their understanding of the interplay between organizational culture, employee fit, engagement, and well-being, providing insights for strategic decision-making and potential collaborations in the field. The robustness and reliability of the results are ensured through the use of recognized bibliometric tools such as VoSviewer and established databases like the Web of Science.